Pengembangan Aplikasi Health Communication Board Berbasis Kendali Pergerakan Linear HEMOCS (Head Movement Control System) - Ivan Putera Pratama; Herman Tolle; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Head Movement Control System (HEMOCS) is a method which utilizes head movements to control objects that exist in a system. In medical treatment cases, Health Communication Board (HCB) acts as a solution that is commonly used by doctors to patients in helping them deliver their desired information. But the solution is apparently not applicable in patients who are experiencing hand physical limitations. Therefore, we propose the development of a similar system with HCB implemented on an iOS mobile device platform which are controlled using the user's head movement. The system will combine the use of mobile devices that implement augmented reality (AR) technology with a Head-Mounted Display (HMD). Head movement types that are recognized by the system including left, right, up, and down head movements. These movements used as a control for user to interact with the system. The results of usability testing has been conducted on five respondents indicated that this application has an average percentage of user satisfaction index of 74.8%, which shows that the use of application provide a satisfactory result for the user.